Fast temperature extraction approach for BOTDA using Generalized Linear Model - Nordin N.D.; Abdullah F.; Zan M.S.D.; Ismail A.; Jamaludin M.Z.; Bakar A.A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Extraction; Photonics; Brillouin frequency shifts; Brillouin optical timedomain analyzer (BOTDA); Conventional methods; Generalized linear model; Measurand; Temperature extraction; Training dataset; Time domain analysis